2020
DOI: 10.1128/jcm.02046-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Cryptococcal Antigen Testing Using Two Novel Semiquantitative Lateral Flow Assays in Persons with Cryptococcal Antigenemia

Abstract: Early cryptococcal disease can be detected via circulating antigen in blood before fulminant meningitis develops, when early antifungal therapy improves survival. Two semiquantitative cryptococcal antigen (CrAg) lateral flow assays (LFAs) have been developed, but their diagnostic performance has not been defined. Cryopreserved serum samples from HIV-infected Ugandans obtained as part of a prospective CrAg-screening cohort were tested in duplicate for CrAg by the CrAgSQ (IMMY) and CryptoPS (Biosynex) lateral fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
4
18
1
Order By: Relevance
“…The median CD4 count of samples in this study was lower than in our cohort (44 cells/µL versus 142 cells/µL), likely resulting in a higher median CrAg titer (1:160 versus 1:80) and contributing to slightly higher observed sensitivity (12). A second study of 99 cryopreserved serum samples from a Ugandan We found moderate specificity of the CryptoPS assay, in keeping with the previous study from Uganda but with greater estimated precision given our larger sample size (11). We carefully followed the…”
Section: Sensitivity and Specificity Of Cryptops In A Sequential Cohosupporting
confidence: 73%
See 3 more Smart Citations
“…The median CD4 count of samples in this study was lower than in our cohort (44 cells/µL versus 142 cells/µL), likely resulting in a higher median CrAg titer (1:160 versus 1:80) and contributing to slightly higher observed sensitivity (12). A second study of 99 cryopreserved serum samples from a Ugandan We found moderate specificity of the CryptoPS assay, in keeping with the previous study from Uganda but with greater estimated precision given our larger sample size (11). We carefully followed the…”
Section: Sensitivity and Specificity Of Cryptops In A Sequential Cohosupporting
confidence: 73%
“…In a small study of patients with a CD4 <100 cells/µL in Cameroon, CryptoPS had good agreement with a commercial lateral flow assay (LFA) (IMMY diagnostics, Norman, Oklahoma, USA) and enzyme immunoassay (EIA) [Premier CrAg, Meridian Bioscience, Inc. Newtown, OH, USA], with a median reciprocal EIA titer >1:160 correlating with T2 band positivity; although the sample size which included on November 6, 2020 by guest http://jcm.asm.org/ Downloaded from just 14 serum CrAg-positive patients limited estimates of precision (10). A second study testing 99 archived serum samples selected from a cohort of HIV-positive Ugandans undergoing CrAg screening reported similar findings, with reasonable agreement between the CryptoPS and IMMY LFA and median CrAg titers of 1:320 in those with T2 band positivity (11); however, this study was also limited by a small sample size. CryptoPS was not tested on whole blood samples likely to be beneficial for point-of-care testing in either study; and the assay has not been evaluated prospectively and under routine care conditions.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Simultaneous detection of anti-mannan antibodies (AMA) improved sensitivity and specificity (83% and 86%) [45], respectively. Several test kits for the detection of mannan antigen (MA) of C. albicans and AMA show variable performance [46][47][48], see [55][56][57][58], which avoid serum pretreatment and support urinary cryptococcal antigen testing, which is useful for screening [59,60]. The LFA is a rapid procedure, there are various test kits on the market, see Table 5;…”
Section: Resultsmentioning
confidence: 99%